Cryptic species of pondweeds (Potamogetonaceae) at an intercontinental scale revealed by molecular phylogenetic analyses. Issue 3 (12th March 2022) - Fehrer, Judith; Iida, Satoko; Kaplan, Zdenek
Abstract: Cryptic species are morphologically indistinguishable but genetically divergent entities that constitute an important part of Earth's biodiversity. They occur in all kingdoms of life, especially when morphological characters are scarce. Compared to the high number of plant species, relatively few cryptic species have been detected so far. Here, we report cryptic species in pondweeds ( Potamogeton ), freshwater aquatic angiosperms that are characterized by reduced morphology. Using four molecular markers (ITS, 5S‐NTS, rpl20‐5′ rps12, trnT‐trnL ), three of them unlinked, we found that the widespread P. octandrus consists of three divergent lineages that correspond to the geographic origins of samples from Africa, Asia, and Australia, respectively. Relatively high genetic divergence between these lineages, reciprocal monophyly and many fixed diagnostic characters indicate that P. octandrus consists of three cryptic species. We formally distinguish the African lineage as P. parvifolius and the Australian lineage as P. tenuicaulis from Asian P. octandrus s.str. Potamogeton tenuicaulis is paraphyletic with the Asian species P. cristatus, which differs by unique fruit characters. We assume that the ancestor of P. cristatus originated from Australia and reached Asia by long‐distance dispersal. Quality criteria for assigning species status to cryptic species and their formal taxonomic recognition are discussed.